1099. Opportunistic Infections Among Long Term Survivors of Kidney Transplantation: Defining Risk Factors. (31st December 2020) - Cheung, Harry; Azar, Marwan M; Gan, Geliang; Deng, Yanhong; Cohen, Elizabeth A; Kulkarni, Sanjay; Malinis, Maricar F
Abstract: Background: Opportunistic infections (OIs) in kidney transplant recipients (KTR) most commonly occur in the early post-transplant period or with increased immunosuppression, largely as a result of impaired T-cell function. Additionally, age confers susceptibility to infection independent of time post-transplant. The combined impact of cumulative immunosuppression and immunosenescence on infection risk of long-term KT survivors has not been well described. Methods: We performed a retrospective chart review of patients age ≥ 18 years who underwent KT between 2003 to 2009 and who survived ≥ 10 years post-KT, in order to evaluate the risk factors for OIs. Demographics, comorbidities, immunosuppression, and clinical data for OIs occurring ≥ 10 years of KT were collected. AST ID Working Group on Infectious Disease Monitoring definitions for OIs was used. Risk factors for OIs were assessed by simple logistic regression. Results: Of 332 KTR, 16 (4.8%) had an OI with 18 total episodes. Of 16 KTR, half were white, 10 (62.5%) were male, median age at time of transplant was 43 (range 25-72) and the median post-transplant follow-up was 14.2 years (range 10.3-37.6). The mean Charlson Comorbidity Index (CCI) at diagnosis was 5.6 (S.D. 3.6). Ten patients (62.5%) were on mycophenolate-based regimens. The mean absolute lymphocyte count (ALC) at the time of OI was 0.78 x 10 3 /µL (S.D. 0.43). Two (12.5%) had acute rejection within 1 year of OI. Of 18 OI episodes, there were 6 PJP, 2 candida esophagitis, 3 CMV (2 viremia, 1 colitis), 2 cryptococcal infections (1 meningitis, 1 myositis/disseminated), 2 adenovirus (pneumonia, colitis), 2 VZV (herpes zoster) and 1 HSV (esophagitis). Two patients had 2 concurrent OIs (1 had PJP and cryptococcus and 1 had HSV and candida esophagitis). Three died within 30-days of OI diagnosis. OI incidence was associated with years from date of transplant [OR 1.3, p=0.002], cerebrovascular disease [OR 4.45, p=0.02], and lower ALC [OR 5.9, p < 0.05]. CCI also trended towards association [OR 1.24, p=0.09]. Table 1: Demographics, comorbidities, immunosuppression, and clinical data for patients with OIs Table 2: Detailed characteristics of each patient with opportunistic infections Conclusion: OIs were infrequently observed beyond 10 years of transplant among long-term survivors of KT. However, OI incidence was associated with poor outcome. Low ALC and a higher burden of comorbidities were risk factors for very late occurrence of OIs in this population. Disclosures: All Authors : No reported disclosures